Geração automática de casos de teste a partir da utilização de SaaS - Pedro Miguel Vieira da Silva (2018)
Nowadays many web applications play a very important role in our society and in the business world. Much of those companies earn large part of their revenues due to their web applications that provide support services that must be maintained and improved over time. Most of these services operate on a large scale and are in constant change due to the environment in which they operate and due to the rapid technological evolution that is always trying to find new ways to improve our lives. Due to these constant changes, it is difficult to estimate the impact of these changes and to maintain the software requirements documents updated. To estimate this impact, it is highly necessary to have requirements traceability information and a good test methodology so that we can analyze the evolution and consistency of our software. This information is not always present in the companies files sometimes because of documents disorder or because of not so well safekeeping information which makes the process of updating requirements very difficult. On the other hand, those changes also produce a negative impact on the testing proccess, since regular alterations to the developed software lead to changes in the developed test cases which makes it harder to produce consistent and reliable test cases. Regression testing is an essential part of the quality process and ensures that code changes do not hurt the existing functionality. Effective regression testing can save a company's time and money. It should become a routine procedure while developing an application. Regression testing includes executing an increasing set of tests along with covering existing functionality until the product is done. Continuous regression testing help teams build software that behaves as intended and remains stable. The main goal of this work is to extract a set of regression tests from web usage to automate the proccess of maintaining and validating software requirements.